Ecosystem services studies in Turkey: A national-scale review - Basak, Esra; Cetin, Nuket Ipek; Vatandaslar, Can; Pamukcu-Albers, Pinar; Karabulut, Armagan Aloe; Caglayan, Semiha Demirba; Besen, Tuba (Elsevier, 2022)
The concept of Ecosystem Services (ES) has gained global importance since the 1990s. Today its link to sustainable development and human welfare is well documented. However, the level of know-how and the scale and effectiveness of practices differ significantly around the globe. The Ecosystem Services Partnership (ESP) National Network of Turkey aims to fill gaps in ES research and foster collaboration among experts in the public and academic sectors and non-governmental organizations. Therefore, a comprehensive review of ES studies was carried out with rigorous literature research. The review of 247 publications showed that ES research has advanced in the last two decades principally as a result of academia's impetus but increasing efforts in the science-policy interface have also supported its integration into diverse policy sectors. Among all ES, regulating ES were studied more intensely due to the growing effects of climate change on leading economic sectors such as agriculture, forestry, and water management. Monetary valuation and trade-off knowledge have remained low, based on the difficulties in data availability and assessment methods. Although protected areas are critical to biodiversity conservation, the ES concept has not been integrated into protected area management. Therefore, the ES knowledge in Turkey needs to be scaled up to cover the national level, with higher stakeholder engagement and more focused implementation driven by political will.
Keywords: National Ecosystem Services Review; Spatial assessment of ecosystem services; Protected areas; Policy sectors evaluations; Turkey